Biofuel Potential of Plants Transformed Genetically with NAC Family Genes - Singh, Sadhana; Grover, Atul; Nasim, M. (Frontiers in Plant Science, 2016)
NAC genes contribute to enhance survivability of plants under conditions of environmental stress and in secondary growth of the plants, thereby building biomass. Thus, genetic transformation of plants using NAC genes provides a possibility to tailor made biofuel plants. Over-expression studies have indicated that NAC family genes can provide tolerance to various biotic and abiotic stresses, either by physiological or biochemical changes at the cellular level, or by affecting visible morphological and anatomical changes, for example by development of lateral roots in a number of plants. Over-expression of these genes also work as triggers for development of secondary cell walls. In our laboratory, we have observed a NAC gene from Lepidium latifolium contributing to both enhanced biomass as well as cold stress tolerance of model plants tobacco. Thus, we have reviewed all the developments of genetic engineering using NAC genes which could enhance the traits required for biofuel plants, either by enhancing the stress tolerance or by enhancing the biomass of the plants. Keywords NAC, Genetically engineered plants, Abiotic stress tolerance, Secondary growth, Cell wall synthesis, Biomass